Effective homological computations on finite topological spaces - Cuevas-Rozo, Julián; Lambán, Laureano; Romero, Ana; Sarria, Humberto (Applicable algebra in engineering, communication and computing, 2023)
The study of topological invariants of finite topological spaces is relevant because they can be used as models of a wide class of topological spaces, including regular CW-complexes. In this work, we present a new module for the Kenzo system that allows the computation of homology groups with generators of finite topological spaces in different situations. Our algorithms combine new constructive versions of well-known results about topological spaces with combinatorial methods used on finite spaces. In the particular case of h-regular spaces, effective and reasonably efficient methods are implemented and the technique of discrete vector fields is applied in order to improve the previous algorithms.